Analisis Persepsi Bendahara Pengeluaran Atas Aspek Kepentingan dan Kinerja Pengguna dan Mitra Perbankan Dalam Penerapan Kartu Kredit Pemerintah - Ali Said; Sutiono Sutiono (Direktorat Sistem Perbendaharaan, 2021)
Abstract The Indonesian government has implemented government credit card since July 2019. This research provides importance and performance analysis of implementing government credit cards in ministries/agencies of Indonesia. This study collected empirical data from an online questionnaire which was distributed to alumni of the expenditure treasurer training organized by the Budget and Treasury Education and Training Center. The selected samples from 222 respondents, was processed using importance and performance analysis. The results of this empirical research shows the performance of KKP holders and the customer service of KKP issuing banks was still below expectations according to the perception of spending treasurers. KKP holders must be provided with intensive socialization on the use of KKP and customer complaint services at KKP issuing banks must be improved. Other results based on non implementing KKP treasurer perceptions, there are still some obstacles faced by ministries/agencies at the implementation of government credit cards. The results of this study cannot be generalized to the implementation of KKP in Indonesia, because of limited number of respondent samples. Abstrak Pemerintah Indonesia telah menerapkan metode pembayaran tagihan dari rekanan pemerintah menggunakan uang persediaan kartu kredit pemerintah mulai bulan Juli tahun 2019. Penelitian ini bertujuan untuk menganalisis kepentingan dan kinerja atas penerapan kartu kredit pemerintah pada kementerian/lembaga. Data penelitian diperoleh melalui kuesioner online yang disebar melalui media sosial whatsapp. Responden penelitian merupakan alumni pelatihan bendahara pengeluaran yang diselenggarakan oleh Pusdiklat Anggaran dan Perbendaharaan. Sebagian sampel penelitian yang berjumlah 222 responden diolah menggunakan analisis kepentingan dan kinerja. Hasil penelitian menunjukkan bahwa kinerja pemegang KKP dan layanan bank penerbit KKP masih di bawah harapan menurut persepsi bendahara pengeluaran. Pemegang KKP harus diberikan sosialisasi penggunaan KKP yang memadai dan layanan keluhan pelanggan pada bank penerbit KKP harus ditingkatkan. Selain itu masih ditemukan beberapa kendala yang dihadapi oleh kementerian/lembaga pada saat penerapan kartu kredit pemerintah. Dengan keterbatasan jumlah sampel responden, maka hasil penelitian ini tidak dapat digeneralisasi untuk penerapan KKP di Indonesia.